Hepatorenal syndrome in hospitalized patients with chronic liver disease: results from the Nationwide Inpatient Sample 2002–2012. Issue 1 (January 2016) - Pant, C; Jani, B S; Desai, M; Deshpande, A; Pandya, Prashant; Taylor, Ryan; Gilroy, R; Olyaee, M
Abstract : Hepatorenal syndrome (HRS) is one of the leading causes of hospitalizations in patients with chronic liver disease (CLD). We conducted a retrospective national database study to determine the epidemiology of HRS in hospitalized patients with CLD. Data from a Nationwide Inpatient Sample were extracted from 2002 to 2012 using ICD-9-CM codes related to CLD and HRS. The following outcomes were examined: in-hospital mortality, total charges, length of stay (LOS), patient demographics, procedures, complications, and comorbidities. Statistical analysis including regression was performed to examine factors associated with HRS. During 2002–2012, hospital discharges related to CLD increased from 407, 246 to 836, 475 with an increase of 37.9% for HRS as a complication in this population. Patients with CLD and HRS had worse outcomes compared with patients with CLD without HRS. This was manifested as a higher mortality rate (32.0% vs 10.3%), increased LOS (median 7 vs 5 days), and increased hospital costs (median 16, 000 vs 11, 000). Logistic regression demonstrated that HIV/AIDS (adjusted OR 2.9, 95% CI 2.2 to 3.9), pneumonia (aOR 2.8, 95% CI 2.3 to 3.2), and esophageal variceal bleeding (aOR 1.9, 95% CI 1.7 to 2.0) were associated with higher mortality in patients with HRS. Conversely, liver transplantation (aOR 0.1, 95% CI 0.1 to 0.1), transjugular intrahepatic portosystemic shunt (aOR 0.5, 95% CI 0.4 to 0.6), and hospitalization in the Midwest region of the USA (aOR 0.7, 95% CI 0.6 to 0.7) were associated with reduced mortality. The incidence of HRS in hospitalized patients with CLD increased during 2002–2012. HRS is associated with significant mortality and morbidity in these patients.